2004
DOI: 10.1021/cm049669l
|View full text |Cite
|
Sign up to set email alerts
|

Multicolored Electrochromism in Polymers: Structures and Devices

Abstract: A review of electrochromic (EC) polymers and their applications in absorption/transmission, reflective, and patterned electrochromic devices (ECDs) is presented. Fundamental properties of EC materials such as optical contrast, coloration efficiency, switching speed, and stability are described along with the commonly used characterization methods. The origin of electrochromism in conjugated polymers is explained in terms of the electronic structure changes in the backbone upon doping/dedoping. The ability to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
526
0
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 776 publications
(544 citation statements)
references
References 92 publications
4
526
0
8
Order By: Relevance
“…This demonstrates that a lower value of intercalated/ deintercalated charge density is adequate enough to bring about a larger optical contrast and this is most advantageous for maximizing the cycling life of the device. This is also corroborated by Argun et al 1 and Rauh et al, 35 as authors also observed that at high doping levels, as percent transmittance saturates, coloration efficiency drops owing to charge consuming side reactions. Further discussion on coloration efficiency of PEDOT-PB and PEDOT-PANI devices can be found in the ESI.w…”
Section: Spectroelectrochemistrysupporting
confidence: 69%
See 1 more Smart Citation
“…This demonstrates that a lower value of intercalated/ deintercalated charge density is adequate enough to bring about a larger optical contrast and this is most advantageous for maximizing the cycling life of the device. This is also corroborated by Argun et al 1 and Rauh et al, 35 as authors also observed that at high doping levels, as percent transmittance saturates, coloration efficiency drops owing to charge consuming side reactions. Further discussion on coloration efficiency of PEDOT-PB and PEDOT-PANI devices can be found in the ESI.w…”
Section: Spectroelectrochemistrysupporting
confidence: 69%
“…1,2 Poly(3,4-ethylenedioxythiophene) or PEDOT in particular has aroused much interest as a cathodic electrochrome due to its rapid and reversible switching between deep-blue and pale-blue hues, the large electronic conductivity of its p-type state, high transmissivity for visible radiation in its oxidized form and the high stability of its doped state. [3][4][5][6] Furthermore, the high insolubility of the polymer also aids in inhibiting its dissolution in the electrolyte during electrochemical cycling.…”
Section: Introductionmentioning
confidence: 99%
“…7 (iii) conducting polymers; among classical electronic conducting polymers (ECPs), the electrochromic properties of polypyrroles, 8 polythiophenes and oligomers, 9 and polyaniline 10 are reported in the literature and (iv) metallopolymers; chromogenic properties typically arise from low-energy metal-to-ligant charge transfer (MLCT), intervalence charge transfer, intraligant excitation and related visible region electronic transitions. 11 …”
Section: Electrochromic Devices and Materialsmentioning
confidence: 99%
“…在实际应用的电致变色器件中, 电致变色材料需要 与离子传导材料配合使用 [2] , 电致变色材料多为刚性分 子链, 离子传导材料多为柔性分子链, 二者之间存在相 容性不佳的问题 [7,8] . 如果能够合成这两类材料的共聚 物, 则可以完美解决这一问题.…”
Section: 引言unclassified